(untitled) (Annals of Medical Research, 2021)
Aim: Aminoglycoside group drugs are widely used due to their broad spectrum and low cost. Clinical or subclinical nephrotoxicity and ototoxicity may frequently be seen as side-effects. The purpose of the present study was to investigate the protective efficacy of thymol and coenzyme Q10 in a gentamycin-induced ototoxicity model in rats. Materials and Methods: Thirty-six female Sprague-Dawley rats were divided into six groups of six animals each. The first group represented the control animals. The second group was exposed to ototoxicity induced by intraperitoneal (i.p.) gentamycin administration at 80 mg/kg for seven days. The third group received oral thymol at 10 mg/kg simultaneously with 80 mg/kg gentamycin. The fourth group received 20 mg/kg oral thymol simultaneously with i.p. 80 mg/kg gentamycin. The fifth group received 10 mg/kg coenzyme Q10 simultaneously with i.p. 80 mg/kg gentamycin, and the sixth group received 20 mg/kg coenzyme Q10 simultaneously with i.p. 80 mg/kg gentamycin. All animals were sacrificed by decapitation under anesthesia at the end of the seventh day. The temporal region was extracted en bloc, and cochlear structures were subjected to histopathological and immunohistochemical examination. Results: Immunohistochemical and histopathological analyses showed that thymol and coenzyme Q10 administered at dosages of 10 mg/kg and 20 mg/kg reduced such effects as hyperemia in the stria vascularis, decreases in inner hair cell numbers, and degeneration in spinal ganglion cells, and produced a decrease in caspase-3 activity. Significantly better results were obtained with high-dose treatments compared to the low-dose groups. The protective efficacy of coenzyme Q10 applied at a dose of 20 mg/kg was particularly marked compared with the ototoxicity group. Conclusion: Coenzyme Q10 and thymol exhibited marked protective effects against ototoxicity induced in rats. Coenzyme Q10 and thymol are two important antioxidant substances with the potential for use in preventing side-effects that may develop in association with gentamycin use.